Serological Survey of the Novel Influenza A H1N1 in Inner City Winnipeg, Manitoba, 2009 - Laura H Thompson; Salaheddin M Mahmud; Yoav Keynan; James F Blanchard; Joyce Slater; Magdy Dawood; Keith Fowke; Paul Van Caeseele; Marissa Becker (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Little is known about the determinants of pandemic H1N1 (pH1N1) infection in Canada among low-income, inner city populations. To inform future influenza planning, the seroprevalence of pH1N1 antibodies among inner city clinic attendees in Winnipeg (Manitoba) according to sociodemographic and risk factor characteristics were estimated and vaccination rates were explored.